Students' Adaptation to Pre Puberty in University Negeri Padang’s Lab-School and its Implications in Guidance and Counseling - Gusnia Yusra; Daharnis Daharnis (Jurnal Neo Konseling, 2019)
Student’s adaptation can be meant as a step of the developmen of teenagers and or pre-puberty in understandingand capable of living or socializing normality, so to get the harmony on themselues and in their environment. The factors which influence the adjustment of the students to pre puberty are. 1) the development of a) body size b) body portion and 2) psychology changing as 1) emotion b) teenagers behaviour on pre puberty. this research uses quentitative descriptive method. the populations of the research are all students of class VII, VIII, and IX junior high scool UNP laboratorium development as many as 397 student.  the sampel technique is taken by simple random sampling as many as 139 student. the data instrument used are questions and analysis data used descriptive method. the result of the research reveals the whole adaptation of the student’s to pre puberty of the students is, considered fairly good. in details are (1) students' adjustment to pre puberty about physical, (2) students' adjustment to pre puberty about psychological changes are both quite good.